Assessing microbial biodiversity in oil palm seedlings using oil palm waste compost mixed media - Siti Suliza Salamat; Mohd Zulkhairi; Mohd Ali Hassan; Mohd Huzairi Mohd Zainudin (ResearchGate, 2024)
Purpose: The oil palm nursery plays a pivotal role in ensuring optimal replanting materials for sustained productivity. However, conventional practices that rely exclusively on inorganic fertilizers can degrade soil over time, highlighting the need to reassess planting materials. This study examines the impact of incorporating compost into soil media on oil palm seedling development in primary nurseries. Method: The study compared microbial biodiversity in soil media with compost amendments by employing DNA sequencing to assess microbial communities. The analysis focused on bacterial species richness and the prevalence of key phyla, including Proteobacteria, Actinobacteria, Acidobacteria, and others. Results: The compost-amended media (T2) demonstrated significantly higher microbial biodiversity, with 60,769 sequences compared to 45,741 sequences in media containing only soil and inorganic fertilizer (T1). This compost-enriched media notably increased bacterial species richness, particularly benefiting nutrientcycling bacteria such as Proteobacteria and Actinobacteria. While Acidobacteria showed sensitivity to compost, other phyla like Firmicutes, Planctomycetes, and Chloroflexi remained stable under the nutrient dynamics of elevated organic content. Streptomyces, known for its metabolic versatility, dominated across all media compositions. The co-occurrence of Bacteroidetes and Acidobacteria in compost-treated soils suggested pH stability that supports plant growth and ecosystem resilience. Conclusion: Integrating compost into nursery media significantly enhances microbial biodiversity and dynamics, particularly favoring beneficial nutrient-cycling bacteria. This suggests that compost amendments can serve as a viable pathway for improving oil palm nursery practices, promoting sustainable soil management, and ensuring long-term productivity.